METHYL ESTER SULFONATE: AN ANIONIC BIOSURFACTANT FOR ENHANCED OIL RECOVERY IN HARSH CONDITION - Muhamad Raihan Al Fikri; Veni Dwi Amelia Putri; Indra Gunawan; Novia Rita; Muslim Abdurrahman (Testing Center for Oil and Gas LEMIGAS, 2025)
Chemical enhanced oil recovery (EOR) is a tertiary phase method used to extract significant amounts of residual crude oil that primary and secondary recovery phases cannot recover. Surfactants are crucial in chemical EOR for their impact on rock surfaces and water-oil interfaces. Optimizing these formulations under reservoir conditions is essential before their use in oil recovery. However, screening is challenging due to the variety of surfactants and their sensitivity to reservoir conditions and rock types. This study introduces methyl ester sulfonate (MES), an anionic bio-surfactant, to improve the oil recovery factor (RF). Spontaneous imbibition (SI) experiments measured MES's ability to enhance oil RF in sandstone reservoir rocks under high salinity and temperature. The results showed MES's excellent performance even under high salinity conditions. On day 14, MES samples under 30 kppm salinity and 80°C with concentrations of 0.5 mM, 2 mM, and 3 mM had RF values of 12%, 18%, and 26%, respectively. Under 40 kppm salinity and 80°C, the RF values were 17%, 19%, and 27%, respectively. MES enhances oil recovery efficiency and preserves environmental health due to its biodegradability, making it a safer alternative to traditional surfactants. Its use can significantly improve chemical EOR processes under challenging conditions. As a novelty, this study also explains the mechanism of MES in changing the wettability of sandstone to the intermolecular scale.